2017
DOI: 10.1002/hec.3586
|View full text |Cite
|
Sign up to set email alerts
|

Do capability and functioning differ? A study of U.K. survey responses

Abstract: SummaryA core feature of the capability approach is that a person's capabilities (what they are able to do and be in their life) can differ from their functionings (what they actually do and are in their life). However, the degree to which capability and functioning differ in practice is unclear. This paper investigates this issue, focusing on capability and functioning differences (CFD) across different aspects of life and different individuals. In the study, the ICECAP‐A capability questionnaire was modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…Research conducted by Van Leeuwen et al [ 47 ] exploring measurement properties of the EQ-5D-3L, ASCOT and ICECAP-O with older adults found that responses to the EQ-5D-3L were more strongly associated with physical health than were responses to the ICECAP-O and ASCOT instruments.. Conversely, mental health status was more strongly associated with responses to the ICECAP-O, whilst self-perceived QoL and mastery was associated more strongly with responses to the ASCOT. Al-Janabi [ 48 ] in his study of 943 family members of meningitis patients, similarly identified that whilst a large proportion of responses indicated that capability equalled functioning (86%) across the dimensions of the ICECAP-A questionnaire, a proportion of responses (12%) demonstrated higher capability than functioning. Participants were more likely to report a difference between their capability and their functioning when their health status was impaired (as indicated by a EQ-5D-5L index score less than 1) as compared to those with unimpaired health status, or if they had caring duties, both groups of people who are likely to be reflected in aged care users.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Van Leeuwen et al [ 47 ] exploring measurement properties of the EQ-5D-3L, ASCOT and ICECAP-O with older adults found that responses to the EQ-5D-3L were more strongly associated with physical health than were responses to the ICECAP-O and ASCOT instruments.. Conversely, mental health status was more strongly associated with responses to the ICECAP-O, whilst self-perceived QoL and mastery was associated more strongly with responses to the ASCOT. Al-Janabi [ 48 ] in his study of 943 family members of meningitis patients, similarly identified that whilst a large proportion of responses indicated that capability equalled functioning (86%) across the dimensions of the ICECAP-A questionnaire, a proportion of responses (12%) demonstrated higher capability than functioning. Participants were more likely to report a difference between their capability and their functioning when their health status was impaired (as indicated by a EQ-5D-5L index score less than 1) as compared to those with unimpaired health status, or if they had caring duties, both groups of people who are likely to be reflected in aged care users.…”
Section: Discussionmentioning
confidence: 99%
“…what people do or are). Functionings may be interpreted more straightforwardly and more uniformly than capabilities, also when older people may think quite differently about their opportunities [21,22]. Capturing functionings also aligns conceptually with often used HRQoL-measures, which are typically based on functionings as well [5].…”
Section: Development Of the Well-being Of Older People Measure (Woop)mentioning
confidence: 90%
“…The authors concluded that subjective capabilities are measurable and that empirical distinctions can made between self-reported capabilities and functionings. To analyze how self-reported capabilities and functionings are perceived to differ, Al-Janabi [41] modified the original version of the ICECAP-Capability measurement tool to assess both capability and functionings for five attributes of a person's life among a United Kingdom-based convenience sample. Results showed that capabilities were larger-than functionings, equaled functionings, or were smaller-than functionings.…”
Section: Measuring Capabilities and Functioningsmentioning
confidence: 99%
“…In analyzing the data, our assumptions were the following: First, the study describes distributions of capabilities and related functionings according to individuals' capital equipment. On the basis of the literature [37,38,41], we assumed that higher educational assets (cultural capital) might enhance capabilities in the respective life domains. As indicated by Chen and Lin [38], this association might also be observable between cultural capital and functionings.…”
Section: Measuring Capabilities and Functioningsmentioning
confidence: 99%